The effects of Pictorial Riddle Type Inquiry Learning and Reciprocal Teaching Learning on Students’ Learning Outcomes - Sari, Arum Puspita; Fadhli, Muhammad (Journal of Innovation in Teaching and Instructional Media, 2021)
The purpose of this quasi-experimental research was to determine whether the mathematics learning outcomes of students taught by Pictorial Riddle type Inquiry learning were higher than the mathematics learning outcomes of students taught by Reciprocal Teaching learning in Class VII SMPN 11 Bengkulu City. The research sample was determined by cluster sampling in order to obtain class VII A as the experimental class and class VII B as the control class. The experimental class of learning was taught with the Pictorial Riddle Inquiry learning model, while the control class was taught with the Reciprocal Teaching learning model. The research data were analyzed using the t test. Based on the data analysis, it’s concluded that the mathematics learning outcomes of students taught by Pictorial Riddle type Inquiry learning are higher than the mathematics learning outcomes of students taught by Reciprocal Teaching learning. In addition, the results of the descriptive analysis also show that the posttest mean score in the experimental class (77.00) is higher than the mean score of posttests obtained in the control class (70.3).